Research on the Impact of Board Governance Model Based on Multi-Internet of Things Perception System on System Risk of Large Business Institutions in China. (2nd June 2022) - Zheng, Dapeng
Abstract : Corporate governance structure is a subject of great theoretical and practical significance, especially the impact of board characteristics on corporate performance, which has been the focus of scholars' attention. However, due to the particularity of China's commercial institutions, especially the state-owned commercial institutions in the transition economy, which have a strong government-led color in system, commercial institutions mainly rely on strengthening the governance of the board of directors to improve the effectiveness of their internal governance. Based on the basic principles of the Internet of Things (IOT) business environment, this paper divides the architecture of multiple IOT perception system into perception domain and business domain. This paper studies the development mode of the economic and business perception system stage of the Internet of Things: the primary stage, the growth and maturity stage, and the integration stage. Strengthen the establishment of an independent director system, create an environment in which independent directors exercise full power, strengthen penalties for violations of directors, strengthen the integrity of directors, and establish a scientific and reasonable board evaluation mechanism. The effective operation of enterprises is based on the perfect market rules and a good market order. The reform of state-owned enterprises with the core of establishing a modern enterprise system and improving corporate governance structure must be carried out simultaneously with the construction of market systems.